Mechanical responses of submarine power cables subject to axisymmetric loadings - Fang, Pan; Jiang, Xiaoli; Hopman, Hans; Bai, Yong (Ocean engineering, 2021)
Submarine power cables are considered lifelines in wind farm engineering, playing a key role in transporting electric current produced by wind turbines or wave converter. Cables inevitably confront combined loadings in deep-sea areas, affecting the integrity and safety during their installation and application. In this paper, the mechanical behaviour of submarine power cables subject to axisymmetric loadings(tension, torsion and external pressure) is investigated through both analytical and numerical methods. The objective of the analytical method is to predict the tension and torsion stiffness of cables and evaluate the stress of armour wires. These values from the two methods are essentially in agreement with each other. In addition, the effects of wire layers, winding angles and external pressure are discussed through the analytical method. The obtained conclusions will benefit the cross-section design of power cables and relative practical engineering. ➢An analytical model considering contact and geometry deformation is proposed to more realistically predict the tension and torsion stiffness of submarine power cables, as well as the wire stress inside.➢A numerical model is built to verify the results from the analytical model and present details of how the cable responds under axisymmetric loadings.➢The parameters that might influence the mechanical behaviour of power cables are investigated through the analytical model and suggestions to optimize the target cable are given.